Evaluation of pyrosequencing for extensive drug resistance-defining anti-tuberculosis drugs for use in public healthcare. (May 2018) - Nambiar, Remya; Shah, Daksha; Ajbani, Kanchan; Kazi, Mubin; Sadani, Meeta; Shetty, Anjali; Keskar, Padmaja; Kamble, Sanjeev; van Belkum, Alex; Rodrigues, Camilla
Abstract: MGIT 960 drug susceptibility testing (DST) for Mycobacterium tuberculosis was compared for performance and speed with pyrosequencing (PSQ). Pulmonary samples (n = 100), from GeneXpert/MTB/Rifampicin-resistant patients receiving second-line treatment for 1–3 months, were subjected to DST and PSQ for seven drugs (isoniazid, rifampicin, kanamycin, amikacin, capreomycin, moxifloxacin, and ofloxacin). The mean time-to-result was 35 and two days for DST and PSQ, respectively. Average concordancy was 92.7%. Theoretically, PSQ showed substantial incremental value over the commercial Genotype MTBDR plus/sl . Mutations not considered in commercial molecular tests were observed by PSQ. Our findings corroborated the association between S315T ( kat G region) and S531L ( rpo B region) and phenotypic resistance. PSQ is more rapid, can be performed from the sample, provides information about all known mutations simultaneously, allows extensive post-processing analyses, and is open to the inclusion of new mutations. It indicates the exact mutation conferring resistance to the particular drug, unlike the qualitative DST.